2014
DOI: 10.7554/elife.04580
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom body output neurons encode valence and guide memory-based action selection in Drosophila

Abstract: Animals discriminate stimuli, learn their predictive value and use this knowledge to modify their behavior. In Drosophila, the mushroom body (MB) plays a key role in these processes. Sensory stimuli are sparsely represented by ∼2000 Kenyon cells, which converge onto 34 output neurons (MBONs) of 21 types. We studied the role of MBONs in several associative learning tasks and in sleep regulation, revealing the extent to which information flow is segregated into distinct channels and suggesting possible roles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
977
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 621 publications
(1,076 citation statements)
references
References 149 publications
(284 reference statements)
55
977
0
Order By: Relevance
“…We next sought to identify individual reward neurons by examining the correlation between induced memory performances and GAL4 expression in all cell types of PAM cluster neurons. To this end, we used a collection of 20 Split-GAL4 driver lines with specific expression in different PAM cluster neurons; the construction and detailed anatomical analysis of these lines are described in Aso et al (33,34). We performed a behavioral screen of thermoactivation in starved flies with this driver collection and measured the formation of STM and LTM.…”
Section: Prediction Of Individual Dopamine Neurons For Ltm Formation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to identify individual reward neurons by examining the correlation between induced memory performances and GAL4 expression in all cell types of PAM cluster neurons. To this end, we used a collection of 20 Split-GAL4 driver lines with specific expression in different PAM cluster neurons; the construction and detailed anatomical analysis of these lines are described in Aso et al (33,34). We performed a behavioral screen of thermoactivation in starved flies with this driver collection and measured the formation of STM and LTM.…”
Section: Prediction Of Individual Dopamine Neurons For Ltm Formation Bymentioning
confidence: 99%
“…Similar to midbrain dopamine neurons in mammals (26,27), the structure and function of PAM cluster neurons are heterogeneous, and distinct dopamine neurons intersect unique segments of the MB lobes (19,(28)(29)(30)(31)(32)(33)(34). Further circuit dissection is thus crucial to identify candidate synapses that undergo associative modulation.…”
mentioning
confidence: 99%
“…For example, spGAL4 combinations have been identified that express in the different neurons innervating the fly mushroom body (Aso et al 2014a) and visual system (Tuthill et al 2013;Nern et al 2015). The activity of each neuron type was then systematically manipulated to assess their contributions to different behaviors (Tuthill et al 2013;Aso et al 2014b). Such approaches facilitate the systematic dissection of neurons that make up specific brain regions, and the assessment of their contributions to behavior.…”
Section: Complementary Approachesmentioning
confidence: 99%
“…Systems have also been developed that direct laser pulses to specific body parts of a moving fly . Other systems restrict light to particular regions of a chamber allowing flies to "choose" whether the neurons are activated (or not) by moving into (or out of) the illuminated region, or coupling neural activation with particular localized features of a larger chamber, such as odors (Suh et al 2007;Lin et al 2013a;Aso et al 2014b;Klapoetke et al 2014;Lin et al 2015).…”
Section: Hardware For Thermo-and Optogenetic Behavioral Experimentsmentioning
confidence: 99%
See 1 more Smart Citation